Pious Children Profile in The Views of the Parents and The Teachers in Elementary Schools - Arie Rakhmat Riyadi (International Journal of Science and Society, 2022)
Understanding the objective conditions of the children's development in schools is the main thing for determining educational goals, content, and strategies. This study aims to provide an overview of the profile of pious children in elementary schools based on the views of the parents and the teachers. This study uses a descriptive method with a quantitative approach. The research subjects were 355 parents, 83 teachers, and 355 students. The object of this research is the character of pious children which consists of five aspects, starting from Jismiyah, Fikriyah, Qolbiyah, Amaliyah, and Maslakiyah. The constructs and instruments used to reveal the data were developed by Riyadi, which has comprehensively involved 20 Panellists and has been empirically tested to have adequate Goodness of Fit (GoF), including standardized instruments that meet high validity and reliability. The results of this study illustrate that the profile of pious children in elementary schools based on the views of parents and teachers is not significantly different, including based on gender and class level (lower and higher class). Several indicators show different results in the view of parents and teachers, especially in the Jismiyah aspect in the body hygiene indicator, then in the Fikriyah aspect, which both agreed to be in the above-average category. This research is directed to become the basis for developing prophetic pedagogy to optimize its goal and significantly develop the character of pious children in elementary schools.